Estado e violência: um estudo sobre o massacre do Carandiru - Onodera, Iwi Mina (2007)
This project analyses the Carandiru Massacre and the historical context that involves the episode. Through evidences here pointed we show the problematic of the autocratical brazilian State and its repressive aparattus, which actuates in the coercion of civil and individual freedom by the use of Military Police, Government organs and its bureaucracy, or by its own social exclusion. We put in context the episode by showing the historical of the brazilian institucional violence, the inoperable penal laws, the problematic of the State of Rights, the failure of the prison sytem and the frequent exposures of the organizations of Human Rights